A Comparison of Women in Nontraditional and Traditional Science Majors: Implications for Career Counsellors - Silcox, Pamela E.; Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examines differences in the career self-efficacy, self-esteem, attitudes toward feminism, and developmental environments of 135 women in traditional (Nursing, Occupational Therapy) and nontraditional (Engineering, Computer Science) science majors. The results indicated that women in traditional and nontraditional science majors did not differ on the variables of career self-efficacy or attitudes toward feminism and self-esteem, although Nursing students reported significantly higher self-esteem than the other groups. Qualitative differences were found in types of career barriers with traditional science majors indicating self- and other-imposed barriers, while nontraditional science majors tended to cite more external barriers.